1986
DOI: 10.1007/bf01762357
|View full text |Cite
|
Sign up to set email alerts
|

On the homogenization of quasilinear divergence structure operators

Abstract: In the Allen-Cahn theory of phase transitions, minimizers partition the domain in subregions, the sets where a minimizer is near to one or to another of the zeros of the potential. These subregions that model the phases are separated by a tiny Diffuse Interface. Understanding the shape of this diffuse interface is an important step toward the description of the structure of minimizers.We assume Dirichlet data and present general conditions on the domain and on the boundary datum ensuring the connectivity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 14 publications
(8 reference statements)
2
57
0
2
Order By: Relevance
“…The aim of homogenization theory is to provide a limiting equation for u 0 . The following result is shown in [14,Theorem 3.6] (see also [29]): there exists a subsequence of {a ε (·, s)} (again indexed by ε) such that the corresponding sequence of solutions {u ε } converges weakly to u 0 in H 1 (Ω), where u 0 is the solution of the so-called homogenized problem…”
Section: Homogenization and Multiscale Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of homogenization theory is to provide a limiting equation for u 0 . The following result is shown in [14,Theorem 3.6] (see also [29]): there exists a subsequence of {a ε (·, s)} (again indexed by ε) such that the corresponding sequence of solutions {u ε } converges weakly to u 0 in H 1 (Ω), where u 0 is the solution of the so-called homogenized problem…”
Section: Homogenization and Multiscale Methodsmentioning
confidence: 99%
“…Rigorously described by the mathematical homogenization theory [12], [31], coarse graining (or homogenization) aims at averaging the finest scales of a multiscale equation and deriving a homogenized equation that captures the essential macroscopic features of the problem as ε → 0. The mathematical homogenization of (1.1) has been developed in [14,10,29] where it is shown that the homogenized equation is of the same quasilinear type as the original equation, with a ε (x, u ε (x)) replaced by a homogenized tensor a 0 (x, u 0 (x)) c XXXX American Mathematical Society depending nonlinearly on a homogenized solution u 0 (the limit in a certain sense of u ε as ε → 0).…”
Section: Introductionmentioning
confidence: 99%
“…The homogenization of linear parabolic operators with almost periodic and random coefficients has been studied in [23,22]. We would like also to mention several results on homogenization of nonlinear elliptic operators [2,5,10,11,15,16]. We would like to note that general elliptic operators in divergence form are considered in [15,16], including random homogenization, while articles [2,5,10,11] are devoted to the homogenization of monotone second-order elliptic operators.…”
Section: Introductionmentioning
confidence: 99%
“…We would like also to mention several results on homogenization of nonlinear elliptic operators [2,5,10,11,15,16]. We would like to note that general elliptic operators in divergence form are considered in [15,16], including random homogenization, while articles [2,5,10,11] are devoted to the homogenization of monotone second-order elliptic operators. For general references in the field of homogenization, we refer to [1,3,6,7,12,17].…”
Section: Introductionmentioning
confidence: 99%
“…Standard homogenization theory for such nonlinear problems [1,2,3] states that u ε converges as ε → 0 (up to a subsequence) weakly in H 1 (Ω) † toward a homogenized solution u 0 which is solution of a one-scale effective problem of the same form as (1),…”
Section: Introductionmentioning
confidence: 99%